Vitamin C – a scoping review for Nordic Nutrition Recommendations 2023 - Jens Lykkesfeldt; Anitra C. Carr (Food & Nutrition Research, 2023)
Vitamin C has multiple metabolic functions in the body, but the available information on the exact relationship between these functions and the intake necessary to maintain them is very limited. However, most attempts to objectively measure adequacy of vitamin C status, including, for example, replacement of metabolic turnover, chronic disease prevention, urinary excretion, and saturation of immune cells and body compartment, currently point toward 50 µmol/L as a reasonable target plasma concentration. As a strong correlation between body weight and vitamin C status exists, recommended intakes (RIs) for other age groups may be extrapolated from the adult RI based on weight. However, as body weights above 70 kg are becoming increasingly common – also in the Nordic region – an RI of 140 mg/day for individuals weighing 100 kg or more should be considered to compensate for the larger volume of distribution. Finally, smoking continues to be a common contributor to poor vitamin C status; therefore, it is proposed that people who smoke increase their daily vitamin C intake by 40 mg/day to compensate for the increased metabolic turnover induced by smoking.